Functional Materials from Nanocellulose: Utilizing Structure–Property Relationships in Bottom‐Up Fabrication - De France, Kevin; Zeng, Zhihui; Wu, Tingting; Nyström, Gustav (Advanced materials (Weinheim), 2021)
It is inherently challenging to recapitulate the precise hierarchical architectures found throughout nature (such as in wood, antler, bone, and silk) using synthetic bottom‐up fabrication strategies. However, as a renewable and naturally sourced nanoscale building block, nanocellulose—both cellulose nanocrystals and cellulose nanofibrils—has gained significant research interest within this area. Altogether, the intrinsic shape anisotropy, surface charge/chemistry, and mechanical/rheological properties are some of the critical material properties leading to advanced structure‐based functionality within nanocellulose‐based bottom‐up fabricated materials. Herein, the organization of nanocellulose into biomimetic‐aligned, porous, and fibrous materials through a variety of fabrication techniques is presented. Moreover, sophisticated material structuring arising from both the alignment of nanocellulose and via specific process‐induced methods is covered. In particular, design rules based on the underlying fundamental properties of nanocellulose are established and discussed as related to their influence on material assembly and resulting structure/function. Finally, key advancements and critical challenges within the field are highlighted, paving the way for the fabrication of truly advanced materials from nanocellulose. As a natural and renewable building block for bottom‐up fabrication, nanocellulose has gained considerable interest for the assembly of sophisticated materials with advanced functionality. The organization of nanocellulose into aligned, porous, and fibrous materials is highlighted, focusing on the inherent material properties enabling the formation of such structures, along with discussing key advancements and critical challenges within the field.